2022
DOI: 10.1097/pec.0000000000002817
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Emergency Medicine Fellowship Program Directors' Viewpoint

Abstract: Objectives: Entrustable Professional Activities (EPAs) are essential tasks physicians perform within their professions. Entrustment levels that pediatric emergency medicine (PEM) fellowship program directors (FPDs) expect graduating fellows to achieve for PEM-specific and common pediatric subspecialty EPAs remain unreported. This study aims to determine minimum entrustment levels FPDs require fellows to achieve to graduate from fellowship and to compare FPD expectations for fellows versus practicing PEM physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…These reports are comparable to pediatric pulmonology and pediatric emergency medicine (PEM) subspecialties. [11,12]In both subspecialties, FPDs indicated that some graduating fellows might need some supervision during practice across all of their subspecialty-speci c EPAs. Additionally, Turner et al reported that FPDs would not require fellows to be able to practice without supervision for graduation for any of the seven common pediatric subspecialty EPAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These reports are comparable to pediatric pulmonology and pediatric emergency medicine (PEM) subspecialties. [11,12]In both subspecialties, FPDs indicated that some graduating fellows might need some supervision during practice across all of their subspecialty-speci c EPAs. Additionally, Turner et al reported that FPDs would not require fellows to be able to practice without supervision for graduation for any of the seven common pediatric subspecialty EPAs.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum level of supervision (LOS) was de ned as the LOS at which no more than 20% of FPDs would want a lower level, which is in agreement with other publications. [11,12,15] The differences in the LOS ratings at graduation and practice for each EPA were analyzed using the Wilcoxon signed-rank tests. The correlation between the number of fellows, years as PD, understanding of EPAs, whether the program uses EPAs, and whether the program participated in the previous SPIN study with graduation and entrustment levels were analyzed using Spearman's correlation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum level of supervision (LOS) was defined as the LOS at which no more than 20% of FPDs would want a lower level, which is in agreement with other publications. [11,12,15] The differences in the LOS ratings at graduation and practice for each EPA were analyzed using the Wilcoxon signed-rank tests. The correlation between the number of fellows, years as PD, understanding of EPAs, whether the program uses EPAs, and whether the program participated in the previous SPIN study with graduation and entrustment levels were analyzed using Spearman's correlation.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have highlighted a need to evaluate the structures and resources of their individual subspecialty training programs to help trainees provide safe and effective care without supervision in practice. [11,12] This study aimed to explore the current opinions about pediatric cardiology (PC) specific EPAs by PC FPDs to help establish consistent expectations for fellows at graduation from fellowship. [13]We hypothesized that the expectations from PC FPD for the minimum LOS for graduation would be lower than the minimum LOS for safe and effective practice.…”
Section: Introductionmentioning
confidence: 99%